The road to clarity: Seventh-Day Adventism in Madagascar - Keller, Eva (Contemporary Anthropology of Religion Ser, 2005)
Several people have joined churches such as the Seventh-day Adventist. This book is an ethnographic study of this phenomenon. It is an account based on almost two years of participation in church members' religious and non-religious lives. It offers an inquiry into the nature of long-term commitment to Adventism among rural people in Madagascar